PENGARUH KEPUASAN KERJA DAN KEDISIPLINAN GURU TERHADAP KINERJA GURU MTs NEGERI DI KABUPATEN MAJALENGKA - Dadang (MADINASIKA, 2019)
Research conducted in Majalengka Regency with the object of research that discusses the operational management of Islamic education related to improving teacher performance through discipline and job satisfaction received. In the formal education pathway (school), the teacher plays an important role, so increasing the teacher represents a key factor in educational success. This specific research aims at the variables of job satisfaction (X1) and work discipline (X2) as independent variables, and teacher performance (Y) as independent variables. This research uses quantitative. The method used to test some participation with a particular sample, sampling techniques are generally carried out randomly, data collection using research instruments, quantitative / statistical data analysis with the aim to test the hypothesis that has been set. The results showed that the contribution of the simultaneous contribution of the variable job satisfaction and teacher discipline to teacher performance by 60.3% and the remaining 39.7% was needed by other factors outside the model shown. The partial role contribution of job satisfaction to teacher performance was 22.265%. The partial contribution of job satisfaction to teacher performance was 37,895%.